Réponses

Meilleure réponse !
  • Utilisateur Brainly
2014-09-01T18:24:51+02:00
A. 
F = (x - 3)² - 16
F= x² - 6x + 9 - 16
F= x² - 6x - 7


C = 4x(2x + 1)²
C= 4x(4x² + 4x + 1)
C= 16x³ + 16x² + 4x

b. 
A= 25x² - 4
A= (5x)² - 2²
A= (5x + 2)(5x - 2)

F= (x - 3)² - 16
F= (x - 3)² - 4²
F= (x - 3 - 4)(x - 3 + 4)
F= (x - 7)(x + 1) 

E= x² - 6x + 9
E= x * x - 2 * 3* x + 3²
E= (x - 3)²
2014-09-01T19:14:28+02:00
Bonjour

Développons

C = 4x(2x+1)^2
C = 4x(4x² + 4x + 1)
C = 16x^3 + 16x² + 4x

F = (x-3)^2-16
F = (x² - 6x + 9) - 16
F = x² - 6x + 9 - 16
F = x² - 6x - 7


Factorisons
A = 25x^2 - 4
A = (5x+2)(5x-2)



E = x^2 -6x+9
E = (x-3)² ou (x-3)(x-3)

F = (x-3)^2-16
F = [(x-3)+4][(x-3)-4]
F = (x-3+4)(x-3-4)
F = (x+1)(x-7)